LAND‐USE SYSTEM AND SPATIAL PLANNING IN FRANCE - Dorosh, O. S.; Loyik, H. K. (Land Management, Cadastre and Land Monitoring, 2013)
Experience of land management and land administration, spatial planning in France is analyzed.